Flood risk assessment using Neutrosophic Analytical Hierarchy Process (N-AHP) and GIS techniques in the Melet Basin (Türkiye) - Murat Fıçıcı (Doğal Afetler ve Çevre Dergisi)
Today, knowing the spatial distribution of flood risk using GIS (Geographic Information Systems)-based MCDM (Multi-Criteria Decision Making) approaches has been a topic addressed by many researchers. In this context, the current study focuses on the spatial distribution of flood risk using the N-AHP (Neutrosophic Analytical Hierarchy Process)-based GIS approach. The Melet Basin (Türkiye) is a case study for the suggested methodology. Four decision-makers used linguistic phrases to compare and assess the flood criteria during the method's application phase. The opinions of the decision makers were combined with the N-AHP, and the criteria were weighted. The results determined that precipitation, distance from the river, drainage density, land use, and slope were the most important factors affecting the flood and contributed approximately 74%. Apart from this, it has been observed that 10% of the basin is in the high and very high flood risk classes, and these risky areas overlap with the flood points of past periods. The proposed approach and findings are anticipated to have theoretical and practical implications.